Asynchronous Teledermatology for Non-Scarring Alopecia: A Retrospective Study - Aliyyat Afolabi; Elijah Brown; Edra K. Ha; Joseph C. English (Telemedicine Reports)
Background: Non-scarring alopecia, including androgenetic alopecia (AGA), alopecia areata (AA), telogen effluvium (TE), and traction alopecia (TA), significantly impacts psychosocial well-being. Access to specialized dermatologic care for these conditions is often limited, particularly in underserved populations. Asynchronous teledermatology has emerged as a potential solution to extend care to these groups. Objective: To evaluate the diagnostic utility and treatment patterns of asynchronous teledermatology for non-scarring alopecia and examine its role in improving care access across diverse populations within the University of Pittsburgh Medical Center (UPMC) network. Methods: A retrospective study of 321 asynchronous teledermatology cases of non-scarring alopecia from 2022 to 2023 was conducted using the UPMC medical record system. Diagnosist, treatment type, and demographic data were analyzed. Longitudinal outcomes and adherence data were not consistently available. Results: AA was the most common diagnosis (59.5%), followed by AGA (26.5%), TE (7.5%), and TA (5.0%). A definitive diagnosis was made remotely in 91.3% of cases; only 8.7% required in-person follow-up. Treatment included over-the-counter therapies such as minoxidil and clobetasol, with prescription medications used for moderate to severe cases. Racial demographics reflected high engagement from Black (22.7%) and Asian (12.9%) patients, with 41.7% of patients residing outside Pittsburgh. Conclusion: Asynchronous teledermatology is an effective tool for diagnosing and managing non-scarring alopecia, facilitating timely intervention and improving access to dermatologic care. Future studies should access patient satisfaction, long-term outcomes, and implementation strategies to further expand equitable teledermatology access.